Passive Keyless Entry Locking Door With ESP32 - Arya Wibisono; MB Nugraha (Ultima Computing : Jurnal Sistem Komputer, 2020)
in this modern era, technology is increasingly sophisticated and can be used by anyone, for example, is a lock that can be bought by anyone and is easy to learn. Therefore, the physical key is getting old and easy to be broken by anyone. By implementing a passive keyless entry system that has been applied to today's cars, adding to the safety and comfort of the car user. we try to apply the system to ESP32 and make digital keys in this research still lacking in card security systems using digital signature algorithms, passive keyless entry systems run as expected by using RFID as input identifier from the UID of each RFID card which is proven to be unique and easy to use.